2021
DOI: 10.3390/membranes11080562
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transporters Beam Signals from Cell Membranes

Abstract: Lipid composition in cellular membranes plays an important role in maintaining the structural integrity of cells and in regulating cellular signaling that controls functions of both membrane-anchored and cytoplasmic proteins. ATP-dependent ABC and P4-ATPase lipid transporters, two integral membrane proteins, are known to contribute to lipid translocation across the lipid bilayers on the cellular membranes. In this review, we will highlight current knowledge about the role of cholesterol and phospholipids of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 171 publications
0
8
0
Order By: Relevance
“…Studies on cholesterol redistribution in lipid rafts have suggested a TMD sterol access site in ABCG1 (Fig. 4) [16,28,52]. Theoretically, ABCG1 intakes sterols from enriched lipid microdomains, relocating them towards the surrounding sterol-deprived membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on cholesterol redistribution in lipid rafts have suggested a TMD sterol access site in ABCG1 (Fig. 4) [16,28,52]. Theoretically, ABCG1 intakes sterols from enriched lipid microdomains, relocating them towards the surrounding sterol-deprived membranes.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, ABC lipid transporters have been shown to alter the composition of their local membrane environment. Such revisions may come from the subduing of lipid rafts by redistributing the high cholesterol content towards the surrounding membrane regions [16,28]. Using in vivo and in vitro functional assays, we have previously characterized a loss-of-function (LOF) mutation ABCG5A540F, a conserved residue near a putative sterol-binding site in ABCG5/G8 [25,29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cholesterol redistribution in lipid rafts have suggested a TMD sterol access site in ABCG1 (Fig. 4) (Ristovski et al, 2021;Sano et al, 2014Sano et al, , 2007. Theoretically, ABCG1 intakes sterols from enriched lipid microdomains, relocating them towards the surrounding sterol-deprived membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Right. Comparison of cholesterol docking pose (light blue) with the cholesterol (green) in the cryo-EM structure [28]. (B) Volumes of transmembrane domain (TMD) cavities found in the of ATP-bound ABCG1 (yellow, PDB ID: 7R8E) and ABCG5/G8 (blue) calculated by MOLE2.5.…”
Section: Supplemental Figurementioning
confidence: 99%
See 1 more Smart Citation